Logistic relationship between tree species diversity of natural areas and human settlements in tropical Mexico - Martínez-Sánchez, José Luis (Instituto de Ecología, A.C., 2019)
Background and Aims: Under the scenario of human population growth, the protected natural areas (ANPs) represent refuges of species; however, they are severely impacted by human settlements <50 km away. Due to the lack of information in Mexico, the effect of the distance and density of the nearest population on the tree diversity of 109 sites of tropical natural areas was analyzed, globally and by vegetation type, and over their surrounding forested area.Methods: By a search with Google Scholar™, documents about six types of tropical forests were selected. One hundred and nine values of sampling area, area of the forest fragment, DBH, α diversity, Shannon, Simpson, and equitability indices, distance to the nearest town, population size and age of the protection decree were extracted. The α diversity was standardized for 1 cm DBH and 1 ha. The sampling area-diversity relationship was analyzed by logarithmic regression, and the biological diversity-distance and population density relationships by logistic regression.Key results: With the analysis of 73 diversity data, α diversity was positively related to the distance and negatively to the size of the population closest to the unprotected natural areas. As distance and size to the closest population increase, the α diversity increases and decreases, respectively. These relationships between size and distance of populations and α diversity were also present individually in the non-protected areas of subdeciduous forest, subhumid, humid, and mountain forest. On the contrary, with the analysis of 36 diversity data for the natural reserves, there was no relationship.Conclusions: This work shows that the distance and density of the population settlement closest to the natural area affect tree diversity, which in 40 years has decreased by 11.4% in the sites analyzed herein. It is discussed how protected areas seem to work in the conservation of biological resources in the tropics of México.